MANAJEMEN BADAN USAHA MILIK DESA (BUMDES) BINA USAHA DESA KEPENUHAN BARAT KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Zul Asvi; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Government of the people of Indonesia have an obligation to explore, cultivate and nurture these natural resources in order to achieve a fair and prosperous society in accordance with the 1945 Constitution Article 33. In an effort to improve the welfare of society, the Government through the agency for Community Empowerment and rural Development form Agency financial Namely Village Owned Enterprises (BUMDes). BUMDes is a financial institution which primary goal is to provide credit loans to people who need to run a business, in addition BUMDes also can establish efforts to improve the local economy. The advantages obtained in writing for the welfare of the members (equalization of capital) and the society through the policy of the Village facilitated by the Provincial Government, the District Government and Village Government. This study aims to determine the management of village owned enterprises BUMDes and the factor that affect the management of village own enterprises BUMDes Bina Usaha Kepenuhan Barat Kecamatan Kepenuhan Rokan Hulu District.Theoretical concept used by the researcher is the concept of management and PrajudiAtmosudirdjo where using indicator Planning, Organizing, Directing, and control. This research uses descriptive qualitative method, using the interview techniques, observation and documentation.Informant of this research using of snowball sampling.The result of this research is that management of Village Owned Enterprise (BUMDes) of Kepenuhan Barat District of Kepenuhan of RokanHulu Regency has not run maximally because seen from indicator of Management indicator that is planning, organizing, directing and control have not run well and factors that Influence according to the researcher is the participation of community and human resources.Keywords: Management, Village Owned Enterprise (BUMDes)